1994
DOI: 10.1136/gut.35.4.506
|View full text |Cite
|
Sign up to set email alerts
|

Specific detection of Mycobacterium paratuberculosis DNA associated with granulomatous tissue in Crohn's disease.

Abstract: The role of mycobacteria,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
1
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(59 citation statements)
references
References 21 publications
(1 reference statement)
2
53
1
1
Order By: Relevance
“…14 The majority of evidence is based on detection of the organism in Crohn's disease patients by immunologic and molecular methods. [15][16][17][18] For example, the IS900 insertion sequence has been detected by polymerase chain reaction (PCR) in intestinal biopsy specimens of Crohn's disease patients. 14,16 However, many of these studies are conflicting and utilize a variety of laboratory techniques without culture confirmation.…”
Section: Introductionmentioning
confidence: 99%
“…14 The majority of evidence is based on detection of the organism in Crohn's disease patients by immunologic and molecular methods. [15][16][17][18] For example, the IS900 insertion sequence has been detected by polymerase chain reaction (PCR) in intestinal biopsy specimens of Crohn's disease patients. 14,16 However, many of these studies are conflicting and utilize a variety of laboratory techniques without culture confirmation.…”
Section: Introductionmentioning
confidence: 99%
“…paratubercuhsis from patients with CD [10] sparked renewed interest in this organism in relation to CD. However, detection of mycobacterial DNA in CD tissue by amplification using Ihe polymerase chain reaction (PCR) has produced conflicting results [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7,9,15,16,19 Other authors have found a variable number of cases, up to 100%, to harbor the organism. 1,3,5,8,[10][11][12][13][14]18 Several reasons may be responsible for the variability in these results. Differences in patient cohorts, techniques, and experimental conditions immediately come to mind.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,8,[10][11][12][13][14] Thus, the finding of MAP DNA in Crohn's disease, including in paraffin-embedded resection specimens, 1,12 still leaves unanswered the question of whether the organism may be environmentally acquired and nonspecifically present. MAP has been cultured from municipal water supplies 11 and pasteurized milk, 25,26 suggesting that it may be ubiquitously present in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation